Human rights in the policy response against Covid-19: discourse analysis of the case of São Paulo, Brazil - Vormittag, Pedro Francisco Moura (2022)
This study examines the policy response to the COVID-19 pandemic enacted by the government of the city of São Paulo, Brazil, from the perspective of its human rights discourse. Through a case study research strategy, we delve into the critical discourse analysis of 491 pieces of municipal legislation enacted with the specific purpose of addressing the global health emergency of COVID-19 in the city of São Paulo between March and October of 2020. We mobilize Norman Fairclough's (1992) text-oriented, three-dimensional critical discourse analysis method to make sense of how human rights law and policy influenced or were influenced by the political choices guiding the city government's handling of the pandemic in the context of the federative battle fought between subnational governments and the central government in Brazil, following up on the findings by Abrucio et al. (2020). We conclude that the policy responses enacted by São Paulo to fight COVID-19 were informed by previous human rights policy frameworks, which contributed to its political effort to adopt a different policy philosophy from the one endorsed by the central government of Brazil under the leadership of President Jair Bolsonaro.